PEMBERDAYAAN MASYARAKAT KELURAHAN DALAM UPAYA PENINGKATAN KESEJAHTERAAN KELUARGA MELALUI PELATIHAN PEMBUATAN KERAJINAN TANGAN DI KELURAHAN TUARA KECAMATAN ENREKANG KABUPATEN ENREKANG - Indih Aminah; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2021)
The Indonesian economy has always been a hot topic of conversation among elements of society. In particular, the condition of Indonesian SMEs is quite apprehensive, with a level of active business of less than 10%. Welfare has always been a benchmark for the economy. The home industry is one of the sectors that have an important role in the development of the Indonesian economy. Proper management in this sector can increase the number of exports of local products, increase the amount of labor absorption, and can increase the income of local farmers. It is estimated that the unemployment rate in Enrekang Regency continues to increase. This shows that the number of job seekers is higher than the number of available jobs. The large population has created various excesses in people's lives, one of which is related to the availability of employment opportunities.